Penerapan Fault Management Untuk Network Management System (NMS) Berbasis Open Source Pada World Wide InteroperabilityFor Microwave Access (WiMAX) - Muhamad Komarudin; Wahyu Eko Sulistiono; Hery Dian Septama (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
Network Management System (NMS) is an application that is used to monitor WiMAX Network and Services. The Network Management model that issued by ISO is the main model that consists of 5 (five) concepts: Fault Management, Configuration Management, Accounting Management, Performance Management and Security Management (FCAPS). The function of Fault Management is to detect, record, notify, and possibly to repair faults in order to maintain the effective network. OpenNMS is an open source NMS application which can be modified to be a Fault Management application which is a standard for WiMAX network. The WiMAX network monitoring is simulated with Net-SNMP using the OID from MIB IEEE 802.16f. The result suggests OpenNMS is applicable to manage faults.